Combination of early Interleukin-6 and -18 levels predicts postoperative nosocomial infection - Yu, Qingwei; Cen, Chaoqun; Gao, Min; Yuan, Hong; Liu, Jingjing (Frontiers in Endocrinology, 2022)
Background The inflammatory response plays a critical role in postoperative nosocomial infections, which are the most common postoperative complications causing adverse events and poor postoperative outcomes. This study aimed to explore the ability of early inflammation-related factor levels to predict the occurrence of nosocomial infections after abdominal surgery. Methods The study included 146 patients with open abdominal surgery (a nosocomial infection group (NI group, n=42) and a no-nosocomial group (NNI group, n=104)). After 1:1 matching, the patients were divided into a matching nosocomial infection group (M-NI group, n=25) and a matching no-nosocomial infection group (M-NNI group, n=25). Serum levels of interleukin (IL)-6, IL-8, IL-10, IL-12, IL-18, macrophage migration inhibitory factor (MIF), and monocyte chemotactic protein (MCP-1) were tested at three time points (pre-operation, 0-hour post-operation (POD1) and 24-hour post-operation (POD2)). The area under the receiver operating characteristic curve (AUC-ROC) was used to test the predictive abilities. Results There were significant differences in the levels of IL-6, IL-12, and IL-18 between the M-NI and M-NNI groups (p < 0.05), but not in the levels of other inflammatory factors. MIF, IL-8, and MCP-1 levels were higher in the M-NI group than in the M-NNI group at POD2 (p < 0.05). In the ROC analysis, the AUC for prediction of nosocomial infection using a combination of IL-6 and IL-18 at POD1 was 0.9616, while the AUCs for IL-6 alone and IL-12 alone were 0.8584 and 0.8256, respectively. Conclusions The combination of the levels of inflammatory factors, IL-6 and IL-18 at the 0-hour postoperative time point significantly improved the predictive of the development of postoperative infection during perioperative. Our study suggests the importance of monitoring postoperative inflammatory markers.